1997
DOI: 10.1210/jcem.82.1.3689
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Activity and Pulsatility of the Hypothalamus-Pituitary-Adrenal System in Male Depressed Patients and Healthy Controls

Abstract: There is only sparse and ambiguous information about circadian and pulsatile secretion features of the hypothalamus-pituitary-adrenocortical system in depression. We studied 15 severely depressed (Hamilton Depression Scale 30.4 +/- 6.7) male patients (age 22-72 yr; mean, 47.7 +/- 14.8) and 22 age-matched male controls (age 23-85 yr; mean, 53.1 +/- 18.2). Twenty-four-hour blood sampling from 0800-0800 h with 30-min sampling intervals was performed; from 1800-2400 h, blood was drawn every 10 min. Multivariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…In young women, both groups have only slightly elevated circadian ACTH and cortisol concentrations (60). However, in an older male depressed population and in elderly males and females, the HPA axis is disturbed, particularly in those with melancholic depression (61)(62)(63). Moreover, cerebrospinal fluid samples from patients with atypical and melancholic depression indicate that atypical depressives have normal CRF and catecholamine concentrations, whereas melancholic depressives have abnormal elevations in both (58,64,65).…”
Section: Do the Effects Of Chronic Stress And Gcs In Rats Apply To Humentioning
confidence: 99%
“…In young women, both groups have only slightly elevated circadian ACTH and cortisol concentrations (60). However, in an older male depressed population and in elderly males and females, the HPA axis is disturbed, particularly in those with melancholic depression (61)(62)(63). Moreover, cerebrospinal fluid samples from patients with atypical and melancholic depression indicate that atypical depressives have normal CRF and catecholamine concentrations, whereas melancholic depressives have abnormal elevations in both (58,64,65).…”
Section: Do the Effects Of Chronic Stress And Gcs In Rats Apply To Humentioning
confidence: 99%
“…Overall, about 20-30% of patients with MDD reveal hypercortisolemia (15,16). Depressed male patients appear to have a more reliable cortisol hypersecretion, raising the issue of sex differences in HPA axis hyperactivity in depressed patients (16,17) (Table 1).…”
Section: How Can Patients' Concomitant Conditions Influence the Diagnmentioning
confidence: 99%
“…A meta-analysis has shown that chronic stress is associated with flatter cortisol slopes across the day, a decreased overall diurnal cortisol level as well as higher cortisol levels in the afternoon and lower levels in the morning (Miller et al, 2007). For example, chronically depressed patients show a decreased or rather flatter decline in cortisol levels across the day (Deuschle et al, 1997; den Hartog et al, 2003). In addition, several studies have demonstrated that lacking positive and supportive relationships with the primary caregivers during childhood can evoke changes of the typical diurnal cortisol pattern, too (Gunnar, 2000; Tarullo and Gunnar, 2006; Roisman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have demonstrated that lacking positive and supportive relationships with the primary caregivers during childhood can evoke changes of the typical diurnal cortisol pattern, too (Gunnar, 2000; Tarullo and Gunnar, 2006; Roisman et al, 2009). Deviations from the typical diurnal cortisol pattern have been found, for example, in traumatized, neglected and abused children (Deuschle et al, 1997; Gunnar and Vazquez, 2001) 3 . To conclude, previous research indicates how important it is to reduce stress in early childhood and to support children’s ability to regulate stress effectively.…”
Section: Introductionmentioning
confidence: 99%